Penerapan E-Commerce oleh UMKM: Systematic Literature Review tentang Faktor Keberhasilan dan Hambatan - Putra, Kharisma Utama; Veri, Jhon (Indo-MathEdu Intellectuals Journal, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in national economic growth. However, in the digital era, MSMEs' adoption of e-commerce remains suboptimal in addressing current challenges. This study aims to identify the factors contributing to success and obstacles in implementing e-commerce by MSMEs through a systematic literature review (SLR) approach. This method was used to analyze 30 relevant international and national journal articles published between 2018 and 2024. These journals were retrieved from credible academic databases such as Scopus and Google Scholar, and then grouped based on key themes or topics emerging from the data. The study results indicate that success factors include management support, digital literacy, technological infrastructure, and customer trust, while key obstacles include limited human resources, implementation costs, and a lack of understanding of digital regulations. This study provides recommendations for the government and stakeholders to support MSMEs digitalization more strategically.